Power transformers behavior under the occurrence of inrush currents and turn-to-turn winding insulation faults - Oliveira, L. M. R. (2014)
This paper intends to provide a detailed characterization of the transformer behavior under the influence of inrush currents and/or incipient winding faults. Experimental and simulation results are presented and discussed. Finally, a promising new method to identify inrush currents, and to distinguish them from internal faults, is suggested.